Single-cell data revealed the regulatory mechanism of TNK cell heterogeneity in liver metastasis from gastric cancer - Jun Gao; Yujuan Liu; Lu Tao; Peng Zeng; Guiying Ye; Ying Zheng; Nai Zhang (Discover Oncology)
Abstract Aim The present work set out to classify cell subpopulations related to liver metastasis from gastric cancer (GC) and the mechanisms of their interactions with other immune cell subpopulations. Background GC is characterized by a high degree of heterogeneity and liver metastasis. Exploring the mechanism of liver metastasis of GC from the perspective of heterogeneity of the tumor microenvironment (TME) might help improve the efficacy of GC treatment. Objective Based on the cellular subpopulation characteristics of GC with liver metastasis, the regulatory mechanisms contributing to GC progression were analyzed, with special focuses on the roles of signaling pathways, transcription factors (TFs) and ligand–receptor pairs. Methods The GSE163558 dataset was downloaded from the Gene Expression Omnibus (GEO) database to collect single-cell transcriptomic data of GC patients and their metastasis groups for cell clustering and relevant analyses. Differentially expressed genes (DEGs) in the GC and GC liver metastasis groups were screened and subjected to Gene Ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) enrichment analysis. SCENIC analysis was used to mine TFs that affected cellular subpopulations during liver metastasis from GC. The relative expression levels of TFs in GC were determined using qRT-PCR. Transwell and wound healing assays were utilized to verify the regulation of the TFs on the migration and invasion of GC cells. Interaction network between the cellular subpopulations was developed applying CellChat. Results Single-cell clustering was performed to group six major cell subpopulations, namely, Myeloid cells, B cells, Mast cells, Epithelial cells, Fibroblasts, and TNK cells, among which the number of TNK cells was significantly increased in the GC liver metastasis group. Differentially enriched pathways of TNK cells between GC and GC liver metastasis groups mainly included IL-17 and Pi3k–Akt signaling pathways. TNK cell subsets could be further categorized into CD8 T cells, Exhausted T cells, NK cells, NKT cells, and Treg cells, with the GC liver metastasis group showing significantly more CD8 T cells and NKT cells. FOS and JUNB were the TFs of TNK cell marker genes that contributed to liver metastasis from GC and the invasion and migration of GC cell lines. Significant differences in immune cell communication ligand–receptor pairs existed between the GC and GC liver metastasis groups. Conclusion This study revealed the critical role of TNK cell subsets in GC with liver metastasis applying single-cell transcriptomics analysis. The findings provided an important theoretical basis for developing novel therapies to inhibit liver metastasis from GC.